PERAN ANGGOTA KELOMPOK WANITA TANI (KWT) MANDIRI DALAM PEREKONOMIAN KELUARGA DI KELURAHAN CEPOKO KECAMATAN GUNUNGPATI KOTA SEMARANG - Anindita, Anggiapsari; Mardiningsih, Dyah; Dalmiyatun, Tutik (Lampung University, 2019)
This research aims to analyze the role of Mandiri woman farmer group members, time allotment for productive and reproductive sector, access and control in family economy. The research wasbegan on 29 November until 29 December 2018 at Mandiri woman farmer group. The research method is a survey with complete enumeration as many as 30 respondents. Data were collected usings questionnaires, depth-interview, observation, documentation, and records. Data were analyzed qualitatively. The research results showed thatmembers of Mandiri woman farmer group in household economy earned average income of Rp1,968,810.00 from participating in the Woman Farmer Group and side bussiness. Thetime spent on productive sector was 6 hours 2 minutes (23.4%) and on reproductive sector was 11 hours 2 minutes (44.3%). On daily basis, women spend their time more on reproductive sector than productive. Members of Mandiri woman farmer group have a high access in reproductive, productive, social, and family economy activities.Keywords: access, control, family economy, role and woman farmer groupThis research aims to analyze the role of Mandiri woman farmer groupmembers, time allotment for productive and reproductive sector, access and control in family economy. The research wasbegan on 29 November until 29 December 2018 at Mandiri woman farmer group. The research method is a survey with complete enumeration as many as 30 respondents. Data were collected usings questionnaires, depth-interview, observation, documentation, and records. Data were analyzed qualitatively. The research results showed thatmembers of Mandiri woman farmer group in household economy earned average income of Rp1,968,810.00 from participating in the Woman Farmer Group and side bussiness. Thetime spent on productive sector was 6 hours 2 minutes (23.4%) and on reproductive sector was 11 hours 2 minutes (44.3%). On daily basis, womenspendtheir time more onreproductive sector than productive. Members of Mandiri woman farmergroup have a high access in reproductive, productive, social, and family economy activities. Keywords: access, control, family economy, role and woman farmer group